2017
DOI: 10.1002/nau.23308
|View full text |Cite
|
Sign up to set email alerts
|

A Pilates exercise program with pelvic floor muscle contraction: Is it effective for pregnant women? A randomized controlled trial

Abstract: Pilates exercise program with PFM contraction is not able to change the PFM strength assessed by manometer in pregnant women, but it improved adherence to the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
(41 reference statements)
1
29
0
5
Order By: Relevance
“…Therefore, within the wide variety of research that has been conducted, our results are in line with those of other authors in this area 28‐34 . These results open the door to broader interventions that investigate regular, scheduled, and supervised physical exercise during pregnancy as a preventive factor for the tears that occur during childbirth.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, within the wide variety of research that has been conducted, our results are in line with those of other authors in this area 28‐34 . These results open the door to broader interventions that investigate regular, scheduled, and supervised physical exercise during pregnancy as a preventive factor for the tears that occur during childbirth.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the study conducted by Dias et al 31 with 50 women, in which Pilates and PFMT exercises were applied, found significant differences (P < .005) in favor of the intervention group in pelvic floor muscle resistance, and in this study, a pressure gauge was used to assess the improvement in the previously mentioned parameter. For the intervention group, the absolute score increased from 3 to 7.5, while that of the control group increased from 4 to 5.8.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The study participants showed improvement in self-esteem, normal daily activities and personal relationships. Dias et al [50] concluded that Pilates exercise program with PFM contraction performed by pregnant women was not capable of changing the PFM strength as assessed by the manometer. The other authors conclude that the effect of combining PFM contraction with hip isometric abduction or adduction does not have the claimed benefit for PFM function [51].…”
Section: Discussionmentioning
confidence: 99%
“…Given the marked increase in practicing Pilates during pregnancy, various studies have been carried out to evaluate its effectiveness [ 14 , 16 , 20 ]. With regard to the specific relation of Pilates with PFD, two studies found a positive impact on the PF musculature during pregnancy [ 21 , 22 ], while another study concluded that the method was a valid means of helping to prevent the dysfunction [ 23 ].…”
Section: Introductionmentioning
confidence: 99%